Forms of Criminal Acts in The Novel Save Me by Caaay and The Novel Janji by Tere Liye (Study of Sociology of Literature) - Rahmah, Yuni; Arisni Kholifatu Amalia Shofiani (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to find various forms of criminal acts contained in two novels, entitled Save Me by Caaay and Janji by Tere Liye. The first novel entitled Save Me was published in June 2023 by publisher Skuad x Akad, while the second novel entitled Janji was published in July 2021 by publisher Sabakgrip. The data found is in the form of text in the two novels, as evidence of the various forms of criminal acts committed. This research uses a qualitative descriptive method and a literary sociology approach with Sigmund Freud's personality theory. Sigmund Freud's personality theory includes three aspects; Id as a biological aspect, Ego as a psychological aspect and Superego as a sociological aspect. The results of the research found various forms of criminal acts in the novel Save Me by Caaay and the novel Janji by Tere Liye, such as theft, fighting, bullying, drunkenness, threats, fraud, violence, harassment, destruction of facilities and murder. This form of criminal action cannot be separated from social, moral, legal and educational values which can provide inspiration for writers and readers. These actions are a reflection of social society that often occurs recently. The novel Save Me and novel Janji teaches mutual respect, help, support, inspiration and the importance of paying attention to cases of bullying that are rife.